2019
DOI: 10.4252/wjsc.v11.i9.677
|View full text |Cite
|
Sign up to set email alerts
|

Tendon stem/progenitor cell ageing: Modulation and rejuvenation

Abstract: Tendon ageing is a complicated process caused by multifaceted pathways and ageing plays a critical role in the occurrence and severity of tendon injury. The role of tendon stem/progenitor cells (TSPCs) in tendon maintenance and regeneration has received increasing attention in recent years. The decreased capacity of TSPCs in seniors contributes to impaired tendon functions and raises questions as to what extent these cells either affect, or cause ageing, and whether these age-related cellular alterations are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 89 publications
(161 reference statements)
1
35
0
Order By: Relevance
“…The incapacity of complete healing derives from the nature of tendon with its poor cellularity, limited vascularization, and low metabolism [ 3 , 4 ]. The cellular component of the tendon is very low, and with age, it tends to diminish and change in morphology, with loss of stemness markers [ 5 , 6 , 7 ]. As the tendon is a mechanosensitive tissue and extracellular matrix (ECM) remodeling is influenced by mechanical stimulation [ 8 , 9 ], prolonged rehabilitation is considered a valid alternative to surgery that offers great support and is more efficient than pharmacological therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incapacity of complete healing derives from the nature of tendon with its poor cellularity, limited vascularization, and low metabolism [ 3 , 4 ]. The cellular component of the tendon is very low, and with age, it tends to diminish and change in morphology, with loss of stemness markers [ 5 , 6 , 7 ]. As the tendon is a mechanosensitive tissue and extracellular matrix (ECM) remodeling is influenced by mechanical stimulation [ 8 , 9 ], prolonged rehabilitation is considered a valid alternative to surgery that offers great support and is more efficient than pharmacological therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in adult life, tendon becomes a specialized tissue with few cells that reduce their communication and synthetic activity [ 7 ]. With aging, TSPCs lose their stem markers, and they undergo a series of changes that affect their healing ability [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tendon is to transmit muscular forces to the bone, permitting joint motion and subsequent body movement [4]. It was thought that the tendon only consists of tenocytes; nevertheless, the recent studies demonstrated that human and mouse tendons contain stem cells, namely, tendon stem/progenitor cells (TSPCs) [5]. In the review contributed by Dr. Zhang and colleagues, the recent advances in the identification and characterization of TSPCs and their interactions with extracellular matrix and mechanical loading were summarized; meanwhile, the authors outlined the challenges in understanding TSPC biology and function in vivo due to the heterogeneity and lack of specific markers and suggested that the mechanobiology of TSPCs and its role in tendon development, growth, repair, and pathology need to be better clarified.…”
mentioning
confidence: 99%
“…These findings supported the important role of altered TSPCs fate in pathological changes of chronic tendinopathy. During the aging process, TSPCs experienced an evident decrease in self-renewal and colony-forming ability and altered multi-differentiation capacity ( Tan et al, 2012 ; Ruzzini et al, 2014 ; Dai et al, 2019 ; Li et al, 2019 ). TSPCs tended to differentiate into osteoblasts with over-passaging, which was a common cell senescence model in vitro ( Tan et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“… Ruzzini et al (2014) indicated that aged TSPCs expressed higher levels of chondrogenic-related gene expression. Although there is no definite conclusion of these variations, the potential roles of altered TSPC differentiation capacity for age-related pathological changes in tendon were speculated ( Dai et al, 2019 ; Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%